“From the tree to the picture”: A STEAM didactic project for Primary Education - Villalba Gómez, José Víctor (2021)
The project "From the tree to the painting" is an interdisciplinary educational innovation project, based on the STEAM education. This project aimed at the last courses of Primary Education, presents an interdisciplinary work between the areas of Sciences and Arts, developing a series of activities that have a common denominator: to know the main landscape of the Vega Alta del Segura of Murcia (Cieza), and its possibilities as a possible source of paper material. This project bases its work on the realization and application of the STEAM educational methodology, combining didactic activities from different areas of knowledge, but linked to science and art. Resulting in a program of 5 sessions, from a didactic output to an artistic exhibition, through the collection of raw material, creation of pulp and by testing with various pictorial techniques.